Assessment of Various Configurations for Locating the Mean Sea Surface Reference in Laser Hydrography - Billard, Brian (The International Hydrographic Review, 2015)
Various scanning configurations for laser-based airborne hydrography are examined to assess the implications of each in establishing an accurate reference against which sea depths may be measured. A configuration in which an infrared laser beam is scanned and co-directional with a green laser beam is found to give a significantly poorer estimation of mean sea surface location than configurations incorporating a fixed vertical wide divergence infrared beam. Furthermore, configurations that use the leading edge of sea subsurface backscatter to give estimates of local sea surface location are shown to be seriously susceptible to variations in the magnitude of that backscatter.